The Effect of Using Observe and Remember Game in Mastering Vocabulary English Students at the Second Grade of SMPN 1 Harau - Dialestari, Rona; Syahrul, Syahrul; Dewi, Merry Prima; Safitri, Loli (Asian Journal of Islamic Studies and Da'wah, 2023)
The vocabulary mastery of English students at the 2nd grade of SMP N 1 Harau was often constrained by the problem of the lack of students’ ability to remember vocabulary. Students had little vocabulary and they thought English was difficult to learn. The researcher tries to offer a strategy for teaching vocabulary by using "observe and remember" games.This research was conducted to know whether there was an effect of using the observe and remember game as a strategy in teaching vocabulary to improve students' vocabulary mastery. The research used a quantitative approach with a research design used a quasi-experimental. In this study, the researcher used 2 classes as the sample class, which consisted of the experimental class and the control class. The results showed that there was a significant effect of using the observe and remember game in mastering vocabulary. The researcher found the mean score of the post-test was 68,00. It was higher than the pre-test was 34,06 and obtained that the t-calculatedwas 14,46 bigger than the t-table was 2.042. It means that the Ha was accepted. In addition, there was a significant difference between the students who were taught by using the observe and remember game (68,00) and the students who were taught without using the observe and remember game (51,58). The observe and remember game was effective to improve students’ vocabulary mastery in the 2nd grade students of SMP N 1 Harau.